وبائيات الليشمانيا الحشوية في مشفى الأسد الجامعي في اللاذقية بين عامي 2010-2014 - تيشوري نورما (Latakia University Journal -Medical Sciences Series, 2018)
يتميز داء الليشمانيا الحشوية بطيف واسع من التظاهرات السريرية والمخبرية ونسب شفاء عالية في حالات التشخيص المبكر . هدف البحث :وصف أهم الموجودات السريرية والوبائية والمتغيرات المخبرية للأطفال المصابين بداء الليشمانيا الحشوية ،تحديد نسبة إيجابية التحري المباشر للطفيلي في نقي العظم في تشخيص المرض . المرضى وطريقة الدراسة :دراسة وصفية راجعة ل 25طفل مقبولين في مشفى الأسد الجامعي في اللاذقية في الفترة مابين حزيران 2010وحتى حزيران 2014 . النتائج :تضمنت الدراسة 25 طفل راجع 23طفل المشفى بترفع حروري بنسبة92%، كان الشحوب (100%) والضخامة الطحالية (97%) أهم الموجودات السريرية بالفحص، التحري المباشر لطفيلي ببزل النقي إيجابي في 88% من الحالات Introduction : Visceral Leishmaniasis (VL) is characterized by a spectrum of clinical features, with high cure rates in early diagnosis . Objective :the objective is to describe the clinical and epidemiological features and laboratory variables of children with visceral leishmaniasis, And to define the importance of a positive direct investigation of the parasite in Bone marrow in the diagnosis of disease . Patients and Methods : It was a case series study of (25) cases of Visceral Leishmaniasis which were hospitalized between June-2010 and June-2014 in Al -Assad University Hospital, Latakia Results : : 25 children were included in this study. Majority of the patients (92%) presented with fever, common findings in physical examination were(100%) Pallor and (97%) splenomegaly The direct investigation of parasite in Bone marrow was positive in (88%) of cases